The mapping of the scientific production about risk factors for delays in child neuromotor development (Research, Society and Development, 2021)
This study aimed to map the scientific production about risks of child neuromotor development delays. This is a revision study, using bibliometric analyses and seeking to measure the indexes of production and dissemination of scientific knowledge about risk factors for delays in child neuromotor development. Articles were searched in the databases PubMed, SciELO, PEDro, and LILACS, using the descriptors: risk factors, child development, and children. Papers selected were in Portuguese, English, and Spanish, published from 2015 to 2020. At first, 3121 articles were found. The study included 37 articles. The most cited risk factors were low educational level of the mother, low socioeconomic level of the family, and little available resources to stimulate the child. From the articles selected, only 13 had been published in journals with impact factors, and there was a reduction in the scientific production on the topic throughout the years. The results suggest that further studies are necessary, with rigid methodological criteria, so they can be published in journals with good impact factors, which would make it easier for a larger public to access them and enable the elaboration of public health policies. It should also be mentioned that, to elaborate efficient public policies to promote integral child development, there must be technical-scientific knowledge regarding the risk factors that interfere with this process. This knowledge must be found in literature and in reliable quality studies.